The Role of Library Management in Providing Textbooks as Learning Resources in Schools - saba_devi32 (JME Jurnal Management Education, 2025)
Library management plays a crucial role in supporting the educational environment by enhancing student literacy and learning outcomes. This study examines the factors supporting and hindering the effective management of a school library. The supporting factors include strong leadership support, a strategically located library, a well-organized space, and regular reading promotion activities that engage students. Teachers also contribute by encouraging students to visit the library for reading and discussion. However, the study identifies several obstacles, such as limited library space, scheduling conflicts between male and female students, and an insufficient number of library staff, which impede the library’s ability to operate effectively. The findings suggest that addressing these challenges through space expansion, better scheduling, and increasing staff capacity can improve the overall functionality and impact of the library in fostering student literacy and academic success.